p16INK4a als Ziel therapeutischer Impfung = Targeting p16(INK4a) by therapeutic vaccination : concept and status of clinical investigations in HPV-associated head and neck cancers - Reuschenbach, Miriam (HNO, 2015)
BackgroundUp to 70 % of oropharyngeal cancers are attributable to human papillomavirus (HPV) infection; however, a therapy specific for patients with HPV-associated cancers is currently not available. Overexpression of the viral oncogenes E6 and E7 results in cellular alterations that represent interesting targets for novel therapies. One consequence of E6/E7 overexpression is strong expression of the cellular protein p16INK4a. The elimination of p16INK4a-expressing tumor cells by the immune system could be achieved through a therapeutic p16INK4a vaccine.ObjectiveThe current article provides an overview of HPV-associated head and neck cancers and the associated p16INK4a expression. Based on this overview, the concept and status of the clinical investigation of therapeutic p16INK4a vaccination is described.Material and methodsIn addition to discussing published literature, a clinical study is described. In this phase I/IIa study, patients with advanced HPV-associated p16INK4a-expressing tumors were vaccinated with a p16INK4a peptide.ResultsHPV-associated head and neck cancers continuously display strong overexpression of the cellular protein p16INK4a. Vaccination with p16INK4a could represent a novel therapy for patients with HPV-associated carcinomas.ConclusionFurther studies will evaluate the clinical efficacy of therapeutic p16INK4a vaccination. Combinations with other immunotherapeutic approaches are interesting considering the modulating role of the immune system, particularly in HPV-associated tumors.